Advanced Communication and Networking Technologies for Vehicular Ad Hoc Networks (VANETs) (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The application potential of vehicular ad hoc networks (VANETs) is extensive in various fields, such as autonomous driving, smart industry, vehicular networking and space technology. Despite the promising prospects, designing productive VANET systems may involve challenges. For example, communication networks must be fault-resistant in order to achieve reliable information distribution; data collection, processing and transmission may incur excessive delay and data loss, which would reduce the reliability of VANETs; ensuring the security and privacy of users in heterogeneous VANETs is not straightforward. With the newest developments in edge computing, 5G communication technologies, reinforcement learning, federated learning and other technologies provide effective solutions to these problems. The goal of this Research Topic is to focus on the security, reliability, resource optimization, sensor topology optimization, sensor information collection and analysis in VANET systems. We particularly welcome the achievements yielded by the investigation of novel communication and networking technologies in VANETs. This Research Topic invites novel contributions from academia and industrial sectors to research, develop and investigate the opportunities, challenges and solutions related to the implementation of innovative architectures, methods, approaches and technologies for VANETs.